Security controls evaluation, testing, and assessment handbook - Johnson, Leighton (Syngress is an imprint of Elsevier, 2016)
This handbook provides an approach to evaluation and testing of security controls to prove they are functioning correctly in today's IT systems. It shows you how to evaluate, examine, and test installed security controls in the world of threats and potential breach actions surrounding all industries and systems. If a system is subject to external or internal threats and vulnerabilities--which most are--then this book will provide a useful handbook for how to evaluate the effectiveness of the security controls that are in place. It provides direction on how to use SP800-53A, SP800-115, DOD Knowledge Service, and the NIST Families assessment guides to implement thorough evaluation efforts for the security controls in your organization. --